Maleficents Personality Changes in Robert Strombergs Maleficent - Wulandari, Tyas; Santoso, Heri Dwi; Ocktarani, Yesika Maya (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Maleficent, directed by Robert Stromberg, tells about a good fairy that in time turns into evil, as she takes revenge on a man she loves after knowing that he betrays her. One on the issues that attract attention deals with the personality of the central character, Maleficent. The major problem in the study deals with what makes the personality changes as well as to what extent that it changes. The study aims at describing to what the influential factors of Maleficents personality changes. The research uses eclectic research approach combining structural and psychological approaches. Meanwhile, qualitative descriptive method is used in the study with the implementation of library research for taking the data content analysis to analyze it. Results showed that in terms of importance, Maleficent was categorized as a main character; meanwhile, in case of role, she was categorized as either protagonist or antagonist. Maleficent is a dynamic character in accordance with the complexity of her personality. As for the characterization, two types of characterization were found such as direct and indirect characterizations. In the direct characterization of hers, Maleficent was described by the narrator as a fairy living in an area called the Moors. On the other side, several methods of indirect characterization employed showed that she the fairy responsible for protecting the life in the Moors. Results of the psychological analysis using Sigmund Freuds psychoanalytic showed that the Id of Maleficent was her desire to love and be loved sincerely; the ego was her will to curse Aurora but still loves Stefan. Meanwhile, the superego was her kindness forcing her to revoke the curse. Two ego defense mechanisms she used include projection, in form of her regret to Stefan projected to Aurora by cursing her, and repression, in form of relieving her anxiety by murdering Stefan.Â